Factors Affecting Interest in Orthodontic Treatment Among Adults in Jakarta - Kusnoto, Joko; Andayani, Lia Hapsari; Kusnoto, Budi (UI Scholars Hub, 2025)
Objectives: The misalignment of teeth and/or jaws caused by abnormalities in the dynamic process of craniofacial growth and development is known as malocclusion. Over half of children and adolescents worldwide experience some form of malocclusion. Orthodontic treatment is the process of adjusting the position of teeth and jaws to achieve optimal occlusion. In recent decades, there has been a global surge in the need for orthodontic treatment among adults. This study aims to evaluate the factors affecting interest in orthodontic treatment among adults in Jakarta. Methods: This cross-sectional study was conducted from October to December 2023. A total of 196 adults were retrieved by purposive sampling from public places located in Jakarta. Self-administered questionnaire was used to collect data on demographic characteristics, knowledge regarding orthodontic treatment, self-perception, psychosocial, and oral disorder factors. Logistic regression analysis was carried out with a level of significance less than 0.05. Results: Majority of respondents had a good level of knowledge regarding orthodontic treatment (63.3%) and were interested in undergoing orthodontic treatment (85.7%). There was a significant association between other opinions about respondents’ dental arrangement and interest in orthodontic treatment (p = 0.018; 95% CI = 0.135 – 0.826). Self-perception factors, oral disorder factors, and demographic characteristics were not significant in predicting interest in orthodontic treatment. Conclusion: For adults in Jakarta, other people's opinion about respondents’ dental arrangements is the only psychosocial factor correlated with interest in orthodontic treatment. The importance of orthodontic care still needs to be improved for adults in Jakarta.